Limiar: entre a transparência e a opacidade nas monotipias de Mira Schendel - Luisa de Godoy Alves (2018)
Mira Schendel (1919-1988), an artist from Switzerland who lived in Brazil, produced in the 1960s about 2000 monotypes, prints made of inked surface with the possibility of only one print. The research proposal is the study of the limiar between transparency and opacity in Mira Schendels monotypes. Therefore, we will strive in this direction, with the purpose of better understanding the poetry in the work developed by Mira. For this, we present the main theoretical operators of the research: Vilém Flusser, in the concept of transparency; Louis Marin (1931-1992) and Philippe Junod (1938-), for both transparency and opacity; And finally, Jeanne Marie Gagnebin (Suíça, 1949-), for the notion of limiar. In this way, we seek to discern the limiar between transparency and opacity, which will be perceived as a poetic resource used by Mira Schendel in her series of monotypes, to which the artist has dedicated herself for about a decade. The images created by Mira, not only is representative of brasilian art, but also, such as the Flusserian analysis, allow us to see concepts such as transparency and opacity, which, thought by the image, make it possible to see beyond, to disturb in its limiar.